A Systematic Review of Testicle Survival Time After a Torsion Event. Issue 12 (December 2019) - Mellick, Larry Bruce; Sinex, James E.; Gibson, Robert W.; Mears, Kim
Abstract : Background: The time window for possible salvage and survival of a torsed testicle is commonly thought to be 6 to 8 hours. However, survival of torsed testicles with or without subsequent atrophy is known to occur outside that critical time window. In this article, we performed a systematic review of the English literature to provide a more accurate understanding of reported time frames of testicle survival after a torsion event. Objectives: The primary research question was to determine the relationship between time to treatment and the rate of survival for testicles of male patients presenting with testicular torsion (TT). Methods: A systematic review of the literature was performed and structured according to PRISMA guidelines. An exhaustive library search was performed after search strategies were developed for multiple databases that included PubMed, Cochrane library, Ovid MEDLINE, Web of Science, and ProQuest Theses and Dissertations. Two different searches were developed including "testicular torsion" and TT with the search term "time" added. Articles specifically reporting TT case series, testicle outcomes, and time to surgical or manual treatment were selected for review. In addition to and preceding the systematic review, an exhaustive manual search of the literature was also performed by the authors. As a result of these searches, a total of 30 studies with data considered relevant to the research question were included. The information extracted from the articles was tabulated with regard to time intervals to treatment and survival outcome. Results: The systematic review process and protocol are reported in this article. A total of 30 studies were found that reported case series of TT patients and their outcomes as well as time to treatment reported in useful time frames. From these reports, a total of 2116 TT patients were culled, and their outcomes and time to treatment are reported. Because the time to treatment was reported variously in different case series, the 3 most common formats for reporting time to treatment and outcome were used. When overlap between the tables existed, the data were tallied and reported cumulatively. When reported in 6-hour intervals (1, 283 patients), survival at 0 to 6 hours was 97.2%; 7 to 12 hours, 79.3%; 13 to 18 hours, 61.3%; 19 to 24 hours, 42.5%; 25 to 48 hours, 24.4%; and greater than 48 hours, 7.4%. Moreover, we reported cumulative survival data based on reporting for all 3 groups of patients. Testicular salvage in the first 12 hours is 90.4%, from 13 to 24 hours survival is 54.0%, and beyond 24 hours survival is 18.1%. Testicle survival after TT was significant beyond the commonly held 6 to 8 hour time frame and even after more than 24 hours of ischemia. Conclusions: Survival of the testicle irrespective of subsequent atrophy, decreased spermatogenesis or impaired endocrine function after TT can be much longer than the 6 to 8 hours that is commonly taught. Our systematic review of the literature demonstrates that survival percentages are significant even past 24 hours of torsion. This information should encourage aggressive management of patients presenting with TT pain that has been ongoing for many hours. Abstract : Supplemental digital content is available in the text.